Mucosal tumour necrosis factor alpha and interleukin-6 in patients with Helicobacter pylori associated gastritis. Issue 12 (December 1991) - Crabtree, J E; Shallcross, T M; Heatley, R V; Wyatt, J I
Abstract : The production of tumour necrosis factor alpha (TNF alpha) and interleukin-6 by human antral mucosa during short term culture in vitro has been measured by enzyme linked immunosorbent assay. TNF alpha and interleukin-6 concentrations in culture supernatants were significantly greater (p less than 0.001) in patients infected with Helicobacter pylori, all of whom had chronic gastritis, than in patients who were H pylori negative with histologically normal gastric mucosa. Among H pylori colonised patients, TNF alpha concentrations were significantly higher in those with active gastritis and neutrophil infiltration into the epithelium than in those with inactive gastritis. In contrast, interleukin-6 concentrations were raised in both active and inactive gastritis. This study shows that H pylori gastritis is associated with increased gastric mucosal production of TNF alpha and interleukin-6 and that the nature of the mucosal cytokine response varies with the immunohistology of the disease. Inflammatory cytokines generated locally within the gastric mucosa could be relevant to the gastric physiology of H pylori infection.